Gwarancje prawne zasady ogólnej zaufania do przedsiębiorcy - Adamiak, Barbara (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The principle of trusting the entrepreneur should be seen as the basis for deriving the presumption of lawful activity. Legal guarantees of an entrepreneur’s lawful activity, established in legal regulations, are preventive in nature. Their establishment has an impact on the entrepreneur’s lawful activity. These guarantees may turn into repressive ones when the entrepreneur breaches the obligations laid down in the law, with legal effects leading to the loss of rights, imposition of penalties, and incurring financial liability.
Keywords: principle of trusting the entrepreneur; legal guarantees; preventive guarantees; repressive guarantees